Drug interactions : protecting yourself from dangerous drug, medication, and food combinations - Gordon, Melanie Apel. (New York : Rosen Pub. Group, 1999)
Discusses illegal and legal drugs (both over-the-counter and prescription), alcohol, and food and explains how to prevent dangerous interactions among these substances.
Includes bibliographical references (p. 62) and index.
Keywords: Drug interactions -- United States -- Juvenile literature; Drug abuse -- United States -- Prevention -- Juvenile literature; Teenagers -- Drug use -- United States -- Juvenile literature; Drug interactions; Drug abuse